2023
DOI: 10.1177/14649934231173849
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Experiences of Environmental Change in Rural Vietnam: An Intergenerational Approach

Abstract: Locally led adaptation is increasingly promoted as an important strategy for addressing the impacts of climate change. However, the understanding of rural realities in the Global South is still limited by insufficient information about the complex and dynamic relationships between rural communities and their environment. These relationships are influenced both by the material aspects of place and by the social and cultural dynamics that shape identities. This paper seeks to address this gap by providing an in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Understanding how residents view climate change is critical for effective climate change adaptation [12]. Previous research has shown that people's perceptions of climate change vary across different demographic and socio-economic groups [13]. It is important to uncover common themes, concerns, and knowledge gaps about climate change awareness among the public [7].…”
Section: 2 Community Perceptions Of Climate Changementioning
confidence: 99%
“…Understanding how residents view climate change is critical for effective climate change adaptation [12]. Previous research has shown that people's perceptions of climate change vary across different demographic and socio-economic groups [13]. It is important to uncover common themes, concerns, and knowledge gaps about climate change awareness among the public [7].…”
Section: 2 Community Perceptions Of Climate Changementioning
confidence: 99%